2001
DOI: 10.1093/emboj/20.19.5383
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomes and ubiquitin are involved in the turnover of the wild-type prion protein

Abstract: Prion diseases propagate by converting a normal glycoprotein of the host, PrP C , into a pathogenic prion' conformation. Several misfolding mutants of PrP C are degraded through the ER-associated degradation (ERAD)±proteasome pathway. In their infectious form, prion diseases such as bovine spongiform encephalopathy involve PrP C of wild-type sequence. In contrast to mutant PrP, wild-type PrP C was hitherto thought to be stable in the ER and thus immune to ERAD. Using proteasome inhibitors, we now show that~10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
3
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(226 citation statements)
references
References 50 publications
11
209
3
3
Order By: Relevance
“…The UPS is involved in the targeted degradation of most short-lived proteins or proteins that fold improperly within the endoplasmic reticulum. Although inhibition of the UPS causes cytosolic PRNP C accumulation, it is unlikely that the degradation of PRNP Sc occurs mainly in the UPS, 35,36 as PRNP Sc aggregates are unable to enter the narrow channel into the proteasome. On the other hand, the UPS has been reported to be impaired in TSEs, 37,38 and it has been demonstrated that both PRNP Sc and aggregated β-sheet-rich recPRNP inhibit the activity of proteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…The UPS is involved in the targeted degradation of most short-lived proteins or proteins that fold improperly within the endoplasmic reticulum. Although inhibition of the UPS causes cytosolic PRNP C accumulation, it is unlikely that the degradation of PRNP Sc occurs mainly in the UPS, 35,36 as PRNP Sc aggregates are unable to enter the narrow channel into the proteasome. On the other hand, the UPS has been reported to be impaired in TSEs, 37,38 and it has been demonstrated that both PRNP Sc and aggregated β-sheet-rich recPRNP inhibit the activity of proteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular environment is likely to play a key role. The host machinery that usually degrades misfolded proteins [210] may eliminate most of the newly converted proteins. Cellular chaperonelike activities might also be involved in the conversion process, as shown in vitro [65, 207].…”
Section: The Conformational Selection Hypothesismentioning
confidence: 99%
“…Thus far, cytosolic PrP aggregates have been reported only in studies performed in vitro. [25][26][27][28] We performed additional analyses to further characterize the PrP C aggregates in b-cells. All PrP inclusions described in vitro to date were similar to aggresomes.…”
Section: Prp C Aggregation In Islets Is Unique To B-cellsmentioning
confidence: 99%